A Study on the Effectiveness of Biofilter Based on Effective Microorganism (EM) and Empty Fruit Bunch (EFB) for Water Quality Improvement: An Application in Open Channel System - Noor Suraya, Romali; Nadiah, Mokhtar; Siti Fatimah, Che Osmi (2012)
Nowadays, clean water resources are reduced due to water pollution problems. The discharge of solid waste and domestic wastewater into the open channel system leads to the surface water problem. This study emphasizes on the utilization of a biofilter system to treat the domestic water before being discharge into river to preserve the sustainability of water bodies. This biofilter is based on the concept of biological treatment involves the use of Effective Microorganism (EM) Mudball and Empty Fruit Bunch (EFB) with other natural occurring materials such as sand & gravel and activated carbon. This compartmentalized system also contains sponge and charcoal. The biofilter is design to be placed in an open drainage system in a residential area where the flow is continuous. Experiment was conducted at Student Residential College (KK3), Universiti Malaysia Pahang where a site scale filtering system was set up to observe the potential of the system in removing pollutants. The experiments were conducted using three increasing quantity variables. The results were analyzed by evaluating the water quality parameters SS, COD, BOD, AN and turbidity in term of their percentages of removal and comparison to Standard A and Standard B of Environmental Quality Act (1974). The results indicated that the biofilter system is most effective in improving the concentration of turbidity and suspended solid where the percentages of removal is as high as 72.42% and 67.31% respectively, followed by COD with 51.63% removal. The performance of the biofilter is also increased with the increasing quantity of filtering media used.